MENANAMKAN BUDAYA LITERASI PADA ANAK DI LINGKUNGAN KELUARGA - Mega Putri; Elan Halid; Rini Wirasty B.; Redo Andi Marta; Zona Rida Rahayu; Suci Dwinitia; Fera Zora (PUAN INDONESIA, 2026)
Literacy is the ability of an individual to read, write, speak, and think critically. Literacy does not merely encompass the ability to read and write, but also includes understanding and utilizing information. Information obtained by an individual should not be accepted uncritically; rather, it must be analyzed in terms of its content and message. Cultivating this habit from an early age significantly influences a child’s development. In daily life, a culture of literacy is something that must be emphasized across all levels of society, including within the family environment. It is crucial to instill this literacy culture from childhood so that individuals grow into adults capable of critically analyzing every piece of information they receive. Jorong Lurah Nan Tigo is a region located in the Kenagarian Salayo, Solok Regency. This community actively engages women through the PKK Lurah Nan Tigo group. The women in this area come from diverse social and family backgrounds, ranging from housewives to working mothers. With such diversity, parenting patterns also vary, which in turn influences the way literacy culture is applied within families. Therefore, it is important to provide understanding to the women of the PKK Lurah Nan Tigo so that the surrounding community recognizes the significance of literacy culture and its application, beginning within the family, particularly by mothers. Mothers play a pivotal role in the family as motivators who can enhance the abilities and skills of their children.